Writing a Thesis with Sound Argument: A Linguistic Analysis of Indonesian Undergraduate Students’ Academic Texts - Widhiyanto, Widhiyanto; Dewi, Desi Surlitasari; Fadilla, Hilda (Journal of English Teaching and Learning Issues, 2024)
Writing a thesis necessitates the presentation of a compelling and well-written argument. The thesis should situate research within the broader field of study and promote some contributions to the field. A student-writer needs to compose a thesis that reports and justifies the research conducted. This study explores how one undergraduate student-writer at an Indonesian university stages meanings to develop a thesis—as a macrogenre, with sound and engaging arguments by using available linguistic resources. It employs tools of text analyses offered by Systemic Functional Linguistics to examine primarily the interpersonal zone of the arguments. This zone is crucial for a writer to stage meanings to engage with others and others’ knowledge in the field of study, utilizing sound arguments as she takes her stances in the academic community. The analysis focused on two key textual features: the organization of meanings to accomplish the social function of the thesis and the utilization of evaluative language resources to engage with others in the literature. This study involved a single respondent, an undergraduate student-writer, as its focus. The analyses indicate that this novice writer employs various linguistic resources to structure her texts in intricate ways. While her argument at the macro-level (the thesis) is structured relatively similar to the typical thesis, significant differences emerge in her micro-level structure. This study revealed additional deviations in her use of linguistic resources for negotiating arguments at the sentence level (micro-level) and below level, including phrase and word levels.